PEMANFAATAN SUMBER BELAJAR BERBASIS TEKNOLOGI INFORMASI PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN MENGGUNAKAN ISPRING PRESENTER - Untung Joko Basuki; Muhammad Sholeh (Universitas Sahid Surakarta, 2014)
The use of information and communication technology in the learning media isnow an alternative in the learning process. In the course of lectures as a lecturer cannot only rely on writing that is always written in the media whiteboard. The show is certainly conventional and monotonous. In order for the learning process interesting,the use of ICT now has become a necessity and can be more interesting in the learning process.The subject of Islamic education taught should also adjust the development of ICT. As an alternative to the development of learning media, Islamic religious educationmaterials will be developed using ISPRing application. ISpring application is an application that packs material created with power point so that the end result of this teaching materials more interesting by displaying multimedia-based teaching materials In writing, this will be discussed the results of the development of teaching materials of Islamic education that has been packaged in power point will be processed to make it more interesting by using iSpring.